Halide-Substituted Grubbs–Hoveyda Catalysts for Aqueous Ring-Closing Metathesis - Okuda, Jun; Ingram, Aaron; Wang, Dong (Synthesis, 2025)
The effect of halide substitution in ionic-substituted second-generation Grubbs–Hoveyda catalysts (GHII catalysts, AquaMet®) on the ring-closing metathesis activity toward N,N-diallyltosylamide in aqueous media was studied by varying the reaction conditions of biological relevance (pH, buffer, salt additives). The activity, as determined by GC–MS analysis, followed the order: bromide > chloride > iodide. The robustness of these complexes, as judged by time-resolved UV–vis absorptions, followed the reverse order: iodide > chloride > bromide. Diiodide-substituted GHII catalysts performed better than the dichloride and dibromide in the ring-closing metathesis of (N-alkenyl)(N-allyl)tosylamides in aqueous buffer solutions. Catalyst decomposition by hydrolysis appears to be suppressed for the diiodo GHII catalyst in aqueous buffer solutions.
Keywords: Alkenes; Carbene complexes; Cyclization; Heterocycles; Homogeneous catalysis; Metathesis